Coexisting psoriasis is associated with an increased risk of hospitalization for patients with inflammatory bowel disease: an analysis of the National Inpatient Sample database. (23rd December 2020) - Edigin, Ehizogie; Asotibe, Jennifer; Eseaton, Precious Obehi; Busari, Olukayode Ahmed; Achebe, Ikechukwu; Kichloo, Asim; Jamal, Shakeel; Patel, Axi
Abstract : This study compares the odds of being admitted for inflammatory bowel disease (IBD) in patients with psoriasis compared with those without psoriasis alone. We also compared hospital outcomes of patients admitted primarily for IBD with and without a secondary diagnosis of psoriasis. Data were abstracted from the National Inpatient Sample (NIS) 2016 and 2017 database to search for hospitalizations of interest using International Classification of Diseases, 10th Revision codes. Multivariate logistic regression model was used to calculate the adjusted OR (AOR) of IBD being the principal diagnosis for hospitalizations with and without a secondary diagnosis of psoriasis. Multivariate logistic and linear regression analyses were used accordingly to compare outcomes of hospitalizations for IBD with and without secondary diagnosis of psoriasis. There were over 71 million discharges included in the combined 2016 and 2017 NIS database. Hospitalizations with a secondary diagnosis of psoriasis have an AOR of 2.66 (95% CI 2.40 to 2.96, p<0.0001) of IBD being the principal reason for hospitalization compared with hospitalizations without psoriasis as a secondary diagnosis. IBD hospitalizations with coexisting psoriasis have similar lengths of stay, hospital charges, need for blood transfusion, and similar likelihood of having a secondary discharge diagnosis of deep venous thrombosis, gastrointestinal bleed, sepsis, and acute kidney injury compared with those without coexisting psoriasis. Patients with coexisting psoriasis have almost three times the odds of being admitted for IBD compared with patients without psoriasis. Hospitalizations for IBD with coexisting psoriasis have similar hospital outcomes compared with those without coexisting psoriasis.